2017
DOI: 10.1016/j.thorsurg.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Quality Indicators in Thoracic Surgery

Abstract: Synopsis This article outlines a structure for assessing thoracic surgical quality and provides an overview of evidence-based quality metrics for surgical care in both lung cancer and esophageal cancer, with a focus on process and outcome measures in the pre-, intra-, and post-operative setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…45 Third, previous study has demonstrated that PET-CT is helpful for detecting regional and distant metastases. 46 In our study, PET-CT was optional for ESCC patients, which may reduce the specificity in detecting of lymph nodes and distant metastases, especially for the distant metastases. Last, the chemotherapy regimens and prescribed doses vary among ESCC patients in this study, which may influence the results.…”
Section: Discussionmentioning
confidence: 93%
“…45 Third, previous study has demonstrated that PET-CT is helpful for detecting regional and distant metastases. 46 In our study, PET-CT was optional for ESCC patients, which may reduce the specificity in detecting of lymph nodes and distant metastases, especially for the distant metastases. Last, the chemotherapy regimens and prescribed doses vary among ESCC patients in this study, which may influence the results.…”
Section: Discussionmentioning
confidence: 93%
“…Timely surgical treatment has been proposed as a quality metric for lung cancer care. 30 , 31 Our study provides evidence that patients with clinical stage I disease should ideally receive resection within 12 weeks from the date of CT imaging that suggests lung cancer. However, there are several caveats to including a 12-week period as a proposed quality measure.…”
Section: Discussionmentioning
confidence: 99%
“…The Cardio-Thoracic speciality has been one of the first ones to introduce and champion the risk-adjusted outcome analysis for monitoring and improving quality of care (16,17). However, there is an increasing interest in investigating the possible inclusion of the patient's perspective in these scores (18).…”
Section: Discussionmentioning
confidence: 99%